Method for preparing porous tantalum carbide ceramic by combining template method with carbon thermal reduction method

Porous tantalum carbide ceramics are prepared by template method combined with carbon thermal reduction method, which solves the problem of poor performance of existing porous ceramics in ultra-high temperature environments, and achieves ceramic materials with high porosity and excellent mechanical properties, which are suitable for industrial applications.

CN119751072AActive Publication Date: 2025-04-04HUNAN TITAN FUTURE TECH CO LTD

Patent Information

Application Number
CN202510239796.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-04
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

Existing porous ceramic materials show the problem of being unable to do so in high temperature environments, especially in ultra-high temperature environments above 2000°C, the mechanical properties and chemical stability of the materials are difficult to maintain. At the same time, the porosity structure and porosity of porous tantalum carbide ceramics are difficult to regulate, and residual carbon impurities are difficult to remove during sintering, affecting the purity and mechanical properties of the material.

Method used

Porous tantalum carbide ceramics were prepared by the template method combined with the carbon heat reduction method, and the carbon heat reduction reaction between the tantalum source and the carbon source was used to generate tantalum carbide ceramics, avoiding the problem of difficulty in sintering and densification caused by covalent bonds during the sintering process of direct use of tantalum carbide powder. At the same time, by controlling the content of tantalum pentoxide, the residual carbon impurities on the template can be effectively removed and the porosity and structure can be regulated.

Benefits of technology

It achieves the high porosity and excellent mechanical properties of porous tantalum carbide ceramics, can maintain stability in high temperature environments, and has no residual carbon impurities, meeting the requirements of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751072A_ABST
    Figure CN119751072A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing porous tantalum carbide ceramic by combining a template method with a carbon thermal reduction method, and relates to the field of carbide porous ceramic materials. The invention discloses a method for preparing porous tantalum carbide ceramic by combining a template method with a carbon thermal reduction method, which comprises the following steps of: dipping a polyurethane foam template with rough pore rib surfaces in tantalum-containing reaction slurry, rolling to extrude redundant slurry, and repeating dipping-pressing for multiple times; drying the polyurethane foam template with the rough hole rib surface after dipping treatment to obtain a tantalum carbide preform; placing the tantalum carbide preform in a high-temperature furnace, vacuumizing, heating by a gradient heating program, preserving heat, sintering, and cooling to obtain porous tantalum carbide ceramic; the method is easy to operate, the porosity of the porous ceramic can be regulated and controlled, carbon impurities left on the template can be removed, and therefore the filtering performance of the tantalum carbide porous ceramic is controlled, the purity of the porous ceramic is improved, and industrial large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of porous carbide ceramic materials, and in particular relates to a method for preparing porous tantalum carbide ceramics by combining a template method with a carbon thermal reduction method. Background Art

[0002] Porous ceramic materials have shown great application potential in many fields due to their excellent physical and chemical properties, such as extremely high melting point, hardness, extraordinary chemical corrosion resistance and high temperature stability. Compared with traditional ceramics, their significantly increased specific surface area, optimized porosity and controllable pore structure not only extend the service life, but also give the material excellent regeneration performance, making it an ideal choice for thermal insulation, electrode construction and high-efficiency filtration. In the industrial world, porous ceramic materials such as zirconium oxide, silicon carbide and aluminum oxide have developed to the mature application stage. They can maintain morphological stability in extremely high temperature environments (1000-1700℃) and show extraordinary heat resistance. Faced with the challenge of higher temperatures (over 2000℃), the existing material system seems to be unable to cope with it, and a breakthrough in new materials is urgently needed.

[0003] Tantalum carbide ceramics are ultra-high temperature ceramics with a melting point of up to 3880°C. They can still maintain good mechanical properties and chemical stability in ultra-high temperature environments above 3000°C, and are widely used in high temperature and semiconductor fields. However, despite the broad prospects, the current research on porous tantalum carbide ceramics is still in its infancy. For example, the document "Adsorption properties and preparation of porous TaC ceramics with regular steps", Ning ~ Ning Yan et al., Journal of Alloys and Compounds, Vol. 731, pp. 971-977, discloses a method for preparing porous TaC ceramics, using carbon powder and tantalum pentoxide as raw materials, and using molding and high-temperature sintering methods to prepare porous tantalum carbide ceramics, but the pore structure of the porous ceramics prepared by this method cannot be adjusted, and the porosity is low, about 65%. Chinese invention patent CN117902916A discloses a porous TaC ceramic material, which combines the molten salt method and the reaction sintering method to prepare porous TaC ceramics at a relatively low temperature, and its porosity can reach more than 90%. However, the porosity of the porous ceramics prepared by this method cannot be controlled, and the strength is relatively low, and it is currently not possible to realize industrial application.

[0004] At present, the commonly used methods for preparing porous materials include adding pore-forming agents, direct foaming, organic foam impregnation, reaction sintering process, sol-gel method, biological template method and 3D printing. Among them, most porous ceramics use organic foam impregnation method, which uses prepared ceramic slurry to impregnate organic foam (usually sponge-like polyurethane), and then burns off the organic matter and sinters the ceramic body to obtain porous ceramic products. This method is not only simple in process and easy to operate, but also does not require complex equipment and has low preparation cost. It is an effective and economical method for preparing high porosity (70-95%) porous ceramics. However, in the process of removing the template, residual carbon impurities may be caused in the sample. If porous ceramics such as zirconium oxide and alumina are sintered in an air atmosphere, these residual carbons are easily oxidized and decomposed. However, when preparing non-oxide porous ceramics, the sintering atmosphere is mostly inert, which makes it difficult to effectively remove the residual carbon impurities, thereby affecting the purity and mechanical properties of the material, which has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing porous tantalum carbide ceramics by combining a template method with a carbon thermal reduction method. The method is simple to operate and can not only regulate the porosity of the porous ceramics, but also remove carbon impurities remaining in the template, thereby controlling the filtration performance of the tantalum carbide porous ceramics and improving the purity of the porous ceramics, thereby realizing industrial-scale production.

[0006] In order to achieve the purpose of the present invention, the present invention provides a method for preparing porous tantalum carbide ceramics by combining a template method with a carbothermal reduction method, which specifically comprises the following steps: S1. Dipping the polyurethane foam template with a rough surface of the pore reinforcement into the reaction slurry containing tantalum, rolling and squeezing out the excess slurry, and repeating the dipping-pressing multiple times; The tantalum-containing reaction slurry is composed of the following raw materials in parts by mass: 30-60% tantalum source, 3-15% carbon source, 1-10% binder, 0.1-1.0% dispersant and 20-50% solvent; the tantalum source is composed of tantalum carbide ceramic powder, tantalum pentoxide and tantalum-containing compound, and the powder particle size is 1-5 μm; the amount of tantalum pentoxide used is 10-30% of the total mass of the tantalum source; the amount of tantalum-containing compound used is 1-10% of the total mass of the tantalum source; the tantalum-containing compound is any one or more of potassium fluorotantalate, tantalum oxyfluoride, tantalum fluoride and tantalum chloride; a tantalum compound mixed with potassium fluorotantalate and tantalum oxyfluoride, wherein the mass ratio of potassium fluorocarbonate is 10-50%; S2. Drying the rough surface of the polyurethane foam template after the impregnation treatment to obtain a tantalum carbide preform, wherein the drying process is as follows: the polyurethane foam template with rough surface of the pores after the impregnation treatment is kept warm for 1 hour at three temperature intervals of 30 to 60°C, 80 to 120°C, and 150 to 220°C, and the heating rate of the three temperature intervals is 5°C / min; S3. Place the tantalum carbide preform in a high-temperature furnace, evacuate it, then heat it with a gradient heating program and keep it warm for sintering, and cool it to obtain a porous tantalum carbide ceramic. The sintering process is: heat it to 500-800°C at a heating rate of 1-5°C / min, and keep it warm for 1 hour; then heat it to 1000-1500°C at a heating rate of 3-10°C / min, and keep it warm for 1 hour; then heat it to 1500-1800°C at a heating rate of 1-5°C / min, and keep it warm for 1 hour; finally heat it to 1800-2500°C at a heating rate of 1-5°C / min, and keep it warm for 2 hours; then cool it to 600°C at a cooling rate of 5°C / min, and then cool it to room temperature with the furnace.

[0007] The present invention utilizes a tantalum source and a carbon source to undergo carbothermal reduction and sintering to generate tantalum carbide ceramics, thereby avoiding the disadvantages of being difficult to sinter and densify due to the strong covalent bonds of tantalum carbide itself during the direct use of tantalum carbide powder for sintering. 2 C and the like have high reactivity and are easy to react with residual carbon sources and sinter.

[0008] Since the binder, dispersant, solvent and polyurethane foam template will decompose and release gas during the sintering process, and the final product after decomposition is carbon, these residual carbons are easily removed by the oxygen reaction in the air when sintering in an air atmosphere, and under the protection of an inert atmosphere, these residual carbons will be retained and dispersed between the ceramic particles, which will eventually make the ceramic particles in the polyurethane foam template skeleton difficult to sinter, and the compressive strength of the prepared porous ceramics will drop sharply. The present invention uses tantalum carbide ceramic powder as a seed crystal in the reaction sintering process, and the remaining tantalum source can react with the carbon source and the residual carbon to finally generate tantalum carbide ceramics, and the tantalum carbide generated by the reaction will gradually grow and sinter with the added tantalum carbide particles as seed crystals.

[0009] The present invention requires special attention during the drying process of the reaction slurry. Too fast or too high a temperature will cause the slurry attached to the skeleton to crack during the drying process, which will eventually lead to a decrease in the mechanical properties of the ceramic. Therefore, the present invention performs insulation treatment at three appropriate temperatures to ensure the adhesion effect of the slurry during the drying process, thereby improving the mechanical properties of the tantalum carbide ceramic of the present invention.

[0010] The specific heating rate curve of the present invention is formulated based on the thermogravimetric analysis curve of the sample. A high-temperature furnace is used to heat and keep warm according to a certain temperature rise curve to ensure that the decomposition of different materials proceeds slowly, thereby avoiding increasing cracks in the ceramic skeleton and decreasing mechanical properties. This ensures that the porous tantalum carbide ceramic of the present invention has a high porosity while also having better mechanical strength.

[0011] The main purpose of the present invention is to optimize the process of preparing porous tantalum carbide ceramics using the template method, and specifically to propose an effective solution to the problem of residual carbon on the porous tantalum carbide ceramic skeleton caused by template decomposition after ceramic sintering. To solve this problem, porous tantalum carbide ceramics were prepared using the template method combined with the carbothermal reduction method, wherein the key raw material required for carbothermal reduction is tantalum pentoxide, and controlling its content can simply and effectively solve the problem of residual carbon.

[0012] Furthermore, the preparation method of the tantalum-containing reaction slurry is: weigh the tantalum source, carbon source, binder, dispersant and solvent according to a certain proportion, mix them evenly and place them in a ball mill for ball milling. During ball milling, the ball-to-material ratio is controlled to be 3 to 5:1, the ball milling speed is 200 to 450 r / min, and the ball milling time is 2 to 8 hours.

[0013] Different tantalum compounds have different melting points and reactivity. Multiple tantalum compounds will react at different temperatures and stages, and couple with the polymer materials volatilized at different stages to promote the sintering of ceramic particles. At the same time, some tantalum compounds such as tantalum chloride can be dissolved in the solvent, making the tantalum source in the slurry more evenly distributed and ensuring that the residual carbon can react completely.

[0014] Furthermore, the carbon source is composed of resin and carbon powder, wherein the resin is selected from phenolic resin and / or furan resin; the usage amount of the resin is 3-10% of the total mass of the carbon source.

[0015] The product of the decomposition of the preferred resin component of the present invention is resin carbon, and the residual carbon rate can reach 30-70%. The decomposed resin carbon has high activity, and the resin can be dissolved in the solvent and evenly wrapped around the tantalum source particles, so that the carbon thermal reduction reaction can be carried out completely and evenly, and the resin can also be used as an adhesive; carbon powder can be used as a carbon source to react with the tantalum source, and can also be used as a filler to reduce the large shrinkage caused by the decomposition of the resin.

[0016] Furthermore, the preparation method of the polyurethane foam template with rough pore rib surface is: add an alkaline solution with a mass concentration of 5 to 30% to the polyurethane foam template for hydrolysis treatment, the hydrolysis temperature is 30 to 80°C, the hydrolysis time is 0.5 to 6 hours, and the polyurethane foam template with rough pore rib surface is obtained after washing and drying.

[0017] Furthermore, the pore density of the polyurethane foam template with rough pore rib surface is any one of 40ppi, 50ppi, 60ppi, 80ppi or 100ppi; the pore density of the polyurethane foam template with rough pore rib surface of the present invention is not limited to the listed ones, and templates with different pore densities can be selected according to needs.

[0018] Furthermore, the alkaline solution is any one or more mixed solutions of potassium hydroxide, sodium hydroxide, barium hydroxide, and magnesium hydroxide.

[0019] In the present invention, the hydrolysis temperature and time are regulated according to the pore density, composition and quality of the polyurethane foam template with rough pore rib surface; due to the influence of the polyurethane preparation process, thin films will remain between the grids of the polyurethane foam template skeleton, and these films will block the impregnated reaction slurry, resulting in uneven impregnation of the reaction slurry. The pore-blocking films can be removed by reacting the polyurethane with an alkali. Polyurethanes with different pore densities and different compositions often contain different fillers, and their reaction activities with alkaline solutions are also different. Therefore, it is necessary to control the quality of the alkaline solution, the hydrolysis temperature and the hydrolysis time; after the hydrolysis, it is necessary to ensure that the thin films between the foam grids are completely removed and the polyurethane foam template skeleton becomes rough, and it is also necessary to ensure that the polyurethane foam template with rough pore rib surface has good compression resilience.

[0020] Furthermore, the binder is composed of a high-temperature binder and a low-temperature binder, wherein the high-temperature binder is 5-10% of the total mass of the reaction slurry containing tantalum, and the low-temperature binder is 0.5-2% of the total mass of the reaction slurry containing tantalum; The high temperature binder is a transition metal or / and an oxide; The low-temperature adhesive is polyacrylamide and / or polyvinyl butyral.

[0021] Furthermore, the transition metal is any one or more of iron, cobalt and nickel; The oxide is any one or more of aluminum oxide, yttrium oxide, and silicon oxide.

[0022] The preferred high-temperature binder of the present invention is mainly used to promote the sintering between tantalum carbide ceramic particles at high temperature; the low-temperature binder is mainly used to fix the reaction slurry on the polyurethane foam template skeleton at low temperature.

[0023] Furthermore, the dispersant is any one or more of fish oil, trioctyl phosphate, and fatty acid; and the dispersant component is soluble in the organic solvent selected in the present invention.

[0024] Further, the solvent is an organic solvent; The organic solvent is selected from any one or more of anhydrous ethanol, ethyl acetate, n-propanol, benzyl alcohol, toluene, phenol, and dimethyl phthalate.

[0025] The present invention can realize phased volatilization of the slurry through a combination of solvents with different boiling points, so that the filler in the slurry can be evenly and densely distributed on the polyurethane foam template skeleton, without causing the slurry attached to the polyurethane foam template skeleton to crack due to an overly fast drying rate, ultimately resulting in excessive cracks in the porous ceramic skeleton after sintering and a decrease in the mechanical properties of the ceramic.

[0026] Furthermore, the above-mentioned rolling extrusion method is: immersing the treated polyurethane foam template with rough surface of hole ribs into the mixed slurry and pressing repeatedly until all holes are filled with slurry, and then putting the template soaked with slurry into a roller press for rolling. The roller gap of the roller press is 20-50% of the thickness of the polyurethane foam template with rough surface of hole ribs. The roller gap needs to be adjusted to an appropriate size according to the viscosity of the slurry. Repeated rolling is performed until the slurry in the polyurethane foam template with rough surface of hole ribs no longer flows out to avoid excess slurry blocking the holes of the template.

[0027] The present invention sets a suitable roller gap and uses a rolling machine to squeeze out excess slurry in the polyurethane foam template with a rough surface of the pores and ribs. The size of the roller gap needs to be adjusted appropriately. It is necessary to squeeze out the excess slurry to reduce pore clogging by the slurry, but it is also necessary to pay attention not to squeeze out the slurry attached to the polyurethane foam template skeleton. Then, through multiple immersion and extrusion, a certain thickness of slurry is finally attached to the polyurethane foam template skeleton.

[0028] The present invention has achieved the following beneficial effects: 1. The preparation process of the present invention is simple, does not require special equipment, and has low cost.

[0029] 2. The porous tantalum carbide ceramics prepared by the present invention have high porosity, and the pore structure and porosity can be controlled. Porous tantalum carbide ceramics of different shapes, sizes and porosities can be designed according to different requirements.

[0030] 3. The porous tantalum carbide ceramics prepared by the present invention have high purity and no residual carbon after the decomposition of the polymer material. The prepared ceramics have high compressive strength and can meet the requirements of industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a backscattered electron image of the tantalum carbide porous ceramic material obtained by the preparation method of Example 1 of the present invention; Figure 2 This is a physical picture of the tantalum carbide porous ceramic material obtained by the preparation method of Example 1 of the present invention; Figure 3 This is a backscattered electron image of the tantalum carbide porous ceramic material obtained by the preparation method of Comparative Example 1 of the present invention; Figure 4This is a physical picture of the tantalum carbide porous ceramic material obtained by the preparation method of Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The porous tantalum carbide ceramic and the preparation method thereof of the present invention are described below in conjunction with specific embodiments.

[0034] Example 1: The preparation method of the porous tantalum carbide ceramic of this example 1 is as follows: 1. Immerse the cut 50ppi polyurethane foam template in 10% NaOH aqueous solution and hydrolyze it in a 50°C water bath for 4 hours. After the hydrolysis is completed, wash it repeatedly with clean water and dry it to obtain a polyurethane foam template with a rough surface of the pores.

[0035] 2. According to the mass ratio of 30:20:2.5:2.5:2:2.5:0.5:0.1:0.2:30:9.7, tantalum carbide (i.e. tantalum carbide ceramic powder), tantalum pentoxide, potassium fluorotantalate, tantalum oxyfluoride, phenolic resin, carbon powder, nickel, trioctyl phosphate, polyvinyl butyral, ethanol and xylene were weighed respectively, and then the weighed samples were placed in a zirconia ball mill, and ball milled at a ball-to-material ratio of 3:1 to obtain a mixed slurry.

[0036] 3. Immerse the treated polyurethane foam template with rough surface of hole reinforcement into the mixed slurry and press repeatedly until all holes are filled with slurry, then put the template soaked with slurry into a roller press and roll it. The roller gap of the roller press is 40% of the thickness of the polyurethane foam template with rough surface of hole reinforcement, and roll it repeatedly until the slurry in the polyurethane foam template with rough surface of hole reinforcement no longer flows out to avoid excess slurry blocking the holes of the template.

[0037] 4. Then put the template soaked in the slurry into the oven for drying. The drying process is: keep warm at 50℃, 80℃, and 160℃ for 1h each, and the heating rate is 5℃ / min.

[0038] 5. After drying, place the sample in a high-temperature carbon tube furnace for vacuum treatment, then heat it to 800°C at a heating rate of 3°C / min and keep it warm for 1 hour; after the insulation is completed, introduce argon gas to a slightly positive pressure, then heat it to 1500°C at a heating rate of 5°C / min and keep it warm for 1 hour; then heat it to 1800°C at a heating rate of 5°C / min and keep it warm for 1 hour; finally, heat it to 2200°C at a heating rate of 3°C / min and keep it warm for 2 hours; then cool it to 600°C at a cooling rate of 5°C / min, then cool it to room temperature with the furnace, and take out the porous tantalum carbide ceramic sample.

[0039] Figure 1 As shown in FIG. 1 , it is a backscattered electron image of a scanning electron microscope of the porous tantalum carbide ceramic material prepared in Example 1. In the image, it can be seen that the skeleton is very clean, and there is no residual carbon or other impurities attached to the surface. Figure 2 The figure shows a physical picture of the tantalum carbide porous ceramic sample prepared in Example 1.

[0040] Example 2: The preparation method of the porous tantalum carbide ceramic of this example 2 is as follows: 1. Immerse the cut 60ppi polyurethane foam template in 10% NaOH aqueous solution and hydrolyze it in a 50°C water bath for 4 hours. After the hydrolysis is completed, wash it repeatedly with clean water and dry it to obtain a polyurethane foam template with a rough surface of the pores.

[0041] 2. According to the mass ratio of 40:20:1.5:3:0.5:0.1:0.2:25:9.7, tantalum carbide, tantalum pentoxide, carbon powder, phenolic resin, nickel, trioctyl phosphate, polyvinyl butyral, ethanol and xylene were weighed respectively, and then the weighed samples were placed in a zirconia ball mill and ball milled at a ball-to-material ratio of 3:1 to obtain a mixed slurry.

[0042] 3. Immerse the treated polyurethane foam template with rough surface of hole reinforcement into the mixed slurry and press repeatedly until all holes are filled with slurry, then put the template soaked with slurry into a roller press and roll it. The roller gap of the roller press is 40% of the thickness of the polyurethane foam template with rough surface of hole reinforcement, and roll it repeatedly until the slurry in the polyurethane foam template with rough surface of hole reinforcement no longer flows out to avoid excess slurry blocking the holes of the template.

[0043] 4. Then put the polyurethane foam template with rough surface of the ribs soaked in slurry into an oven for drying. The drying process is to keep warm at 50℃, 80℃ and 160℃ for 1h each, and the heating rate is 5℃ / min.

[0044] 5. After drying, place the sample in a high-temperature carbon tube furnace for vacuum treatment, then heat it to 800°C at a heating rate of 3°C / min and keep it warm for 1 hour; after the insulation is completed, introduce argon gas to a slightly positive pressure, then heat it to 1500°C at a heating rate of 5°C / min and keep it warm for 1 hour; then heat it to 1800°C at a heating rate of 5°C / min and keep it warm for 1 hour; finally, heat it to 2200°C at a heating rate of 3°C / min and keep it warm for 2 hours; then cool it to 600°C at a cooling rate of 5°C / min, then cool it to room temperature with the furnace, and take out the porous tantalum carbide ceramic sample.

[0045] Embodiment 3: The preparation method of the porous tantalum carbide ceramic of this embodiment 3 is as follows: 1. Immerse the cut 80ppi polyurethane foam template in 10% NaOH aqueous solution and hydrolyze it in a 50°C water bath for 4 hours. After the hydrolysis is completed, wash it repeatedly with clean water and dry it to obtain a polyurethane foam template with a rough surface of the pores.

[0046] 2. According to the mass ratio of 35:20:5:1.5:3:0.5:0.1:0.2:25:9.7, tantalum carbide, tantalum pentoxide, potassium fluorotantalate, carbon powder, furan resin, nickel, trioctyl phosphate, polyvinyl butyral, ethanol and xylene were weighed respectively, and then the weighed samples were placed in a zirconia ball mill and ball milled at a ball-to-material ratio of 3:1 to obtain a mixed slurry.

[0047] 3. Immerse the treated polyurethane foam template with rough surface of hole reinforcement into the mixed slurry and press repeatedly until all holes are filled with slurry, then put the template soaked with slurry into the roller press and roll it. The roller gap of the roller press is 40% of the thickness of the polyurethane foam template with rough surface of hole reinforcement. Repeated rolling until the slurry in the polyurethane foam template with rough surface of hole reinforcement no longer flows out to avoid excess slurry blocking the holes of the template.

[0048] 4. Then put the template soaked in the slurry into the oven for drying. The drying process is to keep warm at 50℃, 80℃ and 160℃ for 1h each, and the heating rate is 5℃ / min.

[0049] 5. After drying, place the sample in a high-temperature carbon tube furnace for vacuum treatment, then heat it to 800°C at a heating rate of 3°C / min and keep it warm for 1 hour; after the insulation is completed, introduce argon gas to a slightly positive pressure, then heat it to 1500°C at a heating rate of 5°C / min and keep it warm for 1 hour; then heat it to 1800°C at a heating rate of 5°C / min and keep it warm for 1 hour; finally, heat it to 2200°C at a heating rate of 3°C / min and keep it warm for 2 hours; then cool it to 600°C at a cooling rate of 5°C / min, then cool it to room temperature with the furnace, and take out the porous tantalum carbide ceramic sample.

[0050] The porosity and compressive strength of the porous tantalum carbide ceramic samples prepared in Examples 1 to 3 above were tested, and the test results are shown in Table 1.

[0051] Table 1 Performance test results of porous tantalum carbide ceramic materials

[0052] Comparative Example 1: The preparation process of the porous tantalum carbide ceramic sample of this comparative example 1 is the same as that of Example 1, and specific reference is made to Example 1. The difference is that the tantalum-containing reaction slurry in this comparative example 1 is composed of tantalum carbide, nickel, trioctyl phosphate, polyvinyl butyral, ethanol, and xylene in a mass ratio of 60:3:0.1:0.2:27:9.7.

[0053] like Figure 3 As shown, it is the backscattered electron image of the scanning electron microscope of the porous tantalum carbide ceramic sample prepared in comparative example 1. In the figure, it can be seen that there are many impurities enriched on the skeleton, and the main component is carbon.

[0054] Comparative Example 2: The preparation process of the porous tantalum carbide ceramic sample of this comparative example 2 is the same as that of Example 1, and specific reference is made to Example 1. The difference is that the tantalum-containing reaction slurry in this comparative example is composed of tantalum pentoxide, carbon powder, phenolic resin, nickel, trioctyl phosphate, polyvinyl butyral, ethanol, and xylene in a mass ratio of 56.5:3:3:0.5:0.1:0.2:27:9.7.

[0055] like Figure 4 , which is a physical picture of the porous tantalum carbide ceramic sample prepared in Comparative Example 2, and shows that the sintered tantalum carbide porous ceramic sample is cracked and broken.

[0056] Comparative Example 3: The preparation process of the porous tantalum carbide ceramic sample of this comparative example 3 is the same as that of Example 1, and specific reference is made to Example 1. The difference is that the drying process of the sample in this comparative example is to place the sample in an oven, then heat it to 120° C. and keep it warm for 5 hours, then take out the sample, and sinter it according to the sintering process of Example 1.

[0057] After sintering, there are no obvious cracks in the sample macroscopically, but the compressive strength is very low, only 0.56MPa.

[0058] Comparative Example 4: The preparation process of the porous tantalum carbide ceramic sample of this comparative example 4 is the same as that of Example 1, and specific reference is made to Example 1. The difference is that the sintering process in this comparative example is to increase the temperature to 800°C at a heating rate of 3°C / min and keep it warm for 1h, during which argon gas is flushed into the furnace until a slight positive pressure is reached, and then the temperature is increased to 2300°C at a rate of 5°C / min and kept warm for 3h, and then cooled to room temperature with the furnace.

[0059] After sintering, the samples shrank unevenly and cracks appeared in some local areas.

[0060] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0061] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing porous tantalum carbide ceramics by combining a template method with a carbothermal reduction method, characterized in that: The specific steps include: S1. Dipping the polyurethane foam template with a rough surface of the pore reinforcement into the reaction slurry containing tantalum, rolling and squeezing out the excess slurry, and repeating the dipping-pressing multiple times; The tantalum-containing reaction slurry is composed of the following raw materials in parts by weight: 30-60% tantalum source, 3-15% carbon source, 1-10% binder, 0.1-1.0% dispersant and 20-50% solvent; The tantalum source is composed of tantalum carbide ceramic powder, tantalum pentoxide and tantalum-containing compounds, and the amount of tantalum pentoxide used is 10-30% of the total mass of the tantalum source; The usage amount of the tantalum-containing compound is 1-10% of the total mass of the tantalum source; the tantalum-containing compound is any one or more of potassium fluorotantalate, tantalum oxyfluoride, tantalum fluoride, and tantalum chloride; S2. Drying the rough surface of the polyurethane foam template after the impregnation treatment to obtain a tantalum carbide preform, wherein the drying process is as follows: the polyurethane foam template with rough surface of the pores after the impregnation treatment is kept warm for 1 hour at three temperature intervals of 30 to 60°C, 80 to 120°C, and 150 to 220°C, and the heating rate of the three temperature intervals is 5°C / min; S3. Place the tantalum carbide preform in a high-temperature furnace, evacuate it, then heat it with a gradient heating program and keep it warm for sintering, and cool it to obtain a porous tantalum carbide ceramic. The sintering process is as follows: heat it to 500-800°C at a heating rate of 1-5°C / min, and keep it warm for 1 hour; after the insulation is completed, introduce argon gas to a slightly positive pressure, and then heat it to 1000-1500°C at a heating rate of 3-10°C / min, and keep it warm for 1 hour; then heat it to 1500-1800°C at a heating rate of 1-5°C / min, and keep it warm for 1 hour; finally, heat it to 1800-2500°C at a heating rate of 1-5°C / min, and keep it warm for 2 hours; then cool it to 600°C at a cooling rate of 5°C / min, and then cool it to room temperature with the furnace.

2. The method for preparing porous tantalum carbide ceramics by combining a template method with a carbon thermal reduction method according to claim 1, characterized in that: The preparation method of the polyurethane foam template with rough pore rib surface is as follows: adding an alkali solution with a mass concentration of 5 to 30% to the polyurethane foam template for hydrolysis treatment, the hydrolysis temperature is 30 to 80° C., the hydrolysis time is 0.5 to 6 hours, and washing and drying to obtain the polyurethane foam template with rough pore rib surface; The pore density of the polyurethane foam template with a rough pore rib surface is any one of 40ppi, 50ppi, 60ppi, 80ppi or 100ppi; The alkaline solution is any one or more mixed solutions of potassium hydroxide, sodium hydroxide, barium hydroxide and magnesium hydroxide.

3. The method for preparing porous tantalum carbide ceramics by combining template method with carbothermal reduction method according to claim 1, characterized in that: The preparation method of the tantalum-containing reaction slurry is as follows: tantalum source, carbon source, binder, dispersant and solvent are weighed in a certain proportion, mixed evenly and placed in a ball mill for ball milling. During ball milling, the ball-to-material ratio is controlled to be 3 to 5:1, the ball milling speed is 200 to 450 r / min, and the ball milling time is 2 to 8 hours.

4. The method for preparing porous tantalum carbide ceramics by combining template method with carbothermal reduction method according to claim 1, characterized in that: The tantalum-containing compound is a mixture of potassium tantalate fluoroate and tantalum oxyfluoride, wherein the mass of the potassium tantalate fluoroate is 10-50% of the mass of the tantalum-containing compound.

5. The method for preparing porous tantalum carbide ceramics by combining template method with carbothermal reduction method according to claim 3, characterized in that: The carbon source is composed of resin and carbon powder, wherein the resin is selected from phenolic resin and / or furan resin; the usage amount of the resin is 3-10% of the total mass of the carbon source.

6. The method for preparing porous tantalum carbide ceramics by combining template method with carbothermal reduction method according to claim 3, characterized in that: The binder is composed of a high-temperature binder and a low-temperature binder; the high-temperature binder accounts for 5-10% of the total mass of the reaction slurry containing tantalum; the low-temperature binder accounts for 0.5-2% of the total mass of the reaction slurry containing tantalum.

7. The method for preparing porous tantalum carbide ceramics by combining template method with carbothermal reduction method according to claim 3, characterized in that: The dispersant is any one or more of fish oil, trioctyl phosphate, and fatty acid; the solvent is an organic solvent; the organic solvent is selected from any one or more of anhydrous ethanol, ethyl acetate, n-propanol, benzyl alcohol, toluene, phenol, and dimethyl phthalate.

Citation Information

Patent Citations

  • Porous TaC ceramic material and preparation method thereof

    CN117902916A

  • Carbon fiber toughened silicon carbide foamed ceramic and preparation method thereof

    CN112500179A

  • High-strength porous silicon carbide ceramic material and preparation method thereof

    CN114195547A

  • Method for preparing silicon carbide foam material through low-temperature sintering

    CN116332668A

  • Method for preparing porous TaC ceramic by using organic foam template method

    CN118652120A

Cited By

  • Method for improving surface bonding strength of ultrahigh-temperature ceramic coating through additive coarsening

    CN120081692A

  • Porous tantalum carbide ceramic based on slurry spraying and preparation method thereof

    CN120647421A

  • Method for preparing porous tantalum carbide ceramic by molten salt assisted template method

    CN121673080A